The processivity of kinesin-2 motors suggests diminished front-head gating. - Muthukrishnan, G.; Zhang, Y.; Shastry, S.; Hancock, W.O. (Current Biology, 2009)
Kinesin-2 motors, which are involved in intraflagellar transport and cargo transport along cytoplasmic microtubules, differ from motors in the canonical kinesin-1 family by having a heterodimeric rather than homodimeric structure and possessing a three amino acid insertion in their neck linker domain. To determine how these structural features alter the chemomechanical coupling in kinesin-2, we used single-molecule bead experiments to measure the processivity and velocity of mouse kinesin-2 heterodimer (KIF3A/B) and the engineered homodimers KIF3A/A and KIF3B/B and compared their behavior to Drosophila kinesin-1 heavy chain (KHC). Single-motor run lengths of kinesin-2 were 4-fold shorter than those of kinesin-1. Extending the kinesin-1 neck linker by three amino acids led to a similar reduction in processivity. Furthermore, kinesin-2 processivity varied inversely with ATP concentration. Stochastic simulations of the kinesin-1 and kinesin-2 hydrolysis cycles suggest that "front-head gating," in which rearward tension prevents ATP binding to the front head when both heads are bound to the microtubule, is diminished in kinesin-2. Because the mechanical tension that underlies front-head gating must be transmitted through the neck linker domains, we propose that the diminished coordination in kinesin-2 is a result of its longer and, hence, more compliant neck linker element.